Intergenerational Spillovers in Disability Insurance - Gordon Boyack Dahl; Anne C. Gielen (Tinbergen Institute, 2018)
Does participation in a social assistance program by parents have spillovers on their children's own participation, future labor market attachment, and human capital investments? While intergenerational concerns have figured prominently in policy debates for decades, causal evidence is scarce due to nonrandom participation and data limitations. In this paper we exploit a 1993 policy reform in the Netherlands which tightened disability insurance (DI) criteria for existing claimants, and use rich panel data to link parents to children's long-run outcomes. The key to our regression discontinuity design is that the reform applied to younger cohorts, while older cohorts were exempted from the new rules. We find that children of parents who were pushed out of DI or had their benefits reduced are 11% less likely to participate in DI themselves, do not alter their use of other government safety net programs, and earn 2% more in the labor market as adults. The combination of reduced government transfers and increased tax revenue results in a fiscal gain of 5,900 euros per treated parent due to child spillovers by 2014. Moreover, children of treated parents complete an extra 0.12 years of schooling on average, an investment consistent with an anticipated future with less reliance on DI. Our findings have important implications for the evaluation of this and other policy reforms: ignoring parent-to-child spillovers understates the long-run cost savings of the Dutch reform by between 21 and 40% in present discounted value terms.
Keywords: I38; H53; J62; 330; Peer effects; disability insurance; intergenerational links